Phytochemicals and Bioactivities of Garcinia latissima Miq. Stem Bark - Neneng Siti Silfi Ambarwati; Asya Aulia Nifa (Novel Aspects on Pharmaceutical Research Vol. 8, 2023)
Purpose: This study focused on the ability to combat bacteria of the ethyl acetate fraction of Garcinia latissima Miq. extract against Bacillus subtilis and Pseudomonas aeruginosa, antioxidant and antibacterial activity against B. subtilis and Staphylococcus aureus from G. latissima Miq. methanolic extract of stem bark, to explore and seek explanations from G. latissima Miq. which inhibits the enzyme elastase. Successive maceration methods carried out plant extraction. Inhibition of elastase enzyme activity was carried out by measuring the kinetics of the enzyme N-succ-(Ala)-3- nitroanilide conversion to p-nitroaniline (substrate) spectrophotometry at 405 nm and using porcine pancreatic elastase (PPE) as an enzyme, to find the potential of natural skin lightening ingredients, from G. latissima Miq. and to assess the antibacterial activity of hexane, ethyl acetate, and methanol extracts from the stem bark of G. latissima Miq. Techniques: For the paper disc defined every bacterium, the diameter of the inhibition zone, while the antibacterial test was done by bioautography, and the minimum inhibitory concentration (MIC) value was established by microdilution. Gradient elution was used for the fractionation, with a silica gel column as the stationary phase. The degree of polarity-based separation was gradually increased while utilizing a combination of the eluents n-hexane, ethyl acetate, and methanol and carried out by column chromatography. The ability to fight bacteria, the fraction of G. latissima Miq. stem bark was tested utilizing bioautography, the inhibition zone approach, and minimal inhibitory concentration. The DPPH (2,2-diphenyl-1picrylhydrazyl) and FRAP (Ferric Reducing Antioxidant Power) techniques were used to assess antioxidant activity—successive maceration methods carried out plant extraction. Inhibition of elastase enzyme activity was carried out by measuring the kinetics of the enzyme N-succ-(Ala)-3- nitroanilide conversion to p-nitroaniline (substrate) spectrophotometry at 405 nm and using porcine pancreatic elastase (PPE) as the enzyme. Bark, fruit, and leaves of G. latissima Miq. extracted by successive maceration. Tyrosinase inhibitory activity assay was measured spectrophotometrically at 490 nm using 3,4-dihydroxy-L-phenylalanine (L-DOPA) as substrate and kojic acid as a positive control. G. latissima Miq. was discovered in Bogor. A multilayer maceration extraction method is used in this investigation. The diffusion and broth dilution methods were used to evaluate antimicrobial activity. According to the findings, G. latissima Miq. methanol extract and extract of ethyl acetate are active as elastase enzyme inhibitors. G. latissima Miq. extract can maintain skin elasticity. Conclusion: The results of this study reveal the most beneficial details and encourage the long-term use of G. latissima Miq. bark in conventional medicinal systems.